A review on the current dental treatment practices in adults and adolescents with obesity - Gizem Ayan; Burak Dayi; Ibrahim Sahin (Medicine Science, 2021)
Obesity is a disease characterized by abnormal fat increase and its prevalence is increasing globally. Excessive and malnutrition habits, insufficient physical activity, and numerous genetic, environmental, socio-cultural and psychological factors are effective in the etiology of obesity. Obesity is associated with various systemic diseases such as high blood pressure, coronary heart diseases, and respiratory diseases. Obesity may also cause oral diseases such as tooth cavity, loss of teeth, periodontitis, xerostomia, traumatic tooth injuries, bruxism, and dental erosion. Some risk factors related to diet are determinant in the correlation between obesity and oral diseases. With the increasing prevalence of obesity, dentists encounter individuals with obesity more often in clinics. Dental clinics should be designed suitable for the treatments of individuals with obesity in terms of accessibility, the comfort of waiting rooms, the ergonomic structure of units. Comorbid systemic diseases in individuals with obesity, and drugs used to require some specific approaches in conservative and surgical treatments. Dentists should perform dental treatments considering the effect of obesity on oral and dental health. This study aimed to examine dental treatment practices in adults and adolescents with obesity in line with the literature. [Med-Science 2021; 10(2.000): 658-61]